Earthworm species (Crassilitellata) from Eastern Amazonia and Northern Cerrado, Brazil - Sousa, Sandriel Costa; Hernández-García, Luis Manuel; Beckman, Ruana Aretha Farias Santiago; Rousseau, Guillaume Xavier (Zootaxa, 2026)
Earthworms are main contributors to the pedogenesis. However, knowledge regarding their diversity and distribution in many regions of Brazil remains limited. This study aimed to report new records and assess the abundance of earthworm species in the eastern Amazon, northern Maranhão Cerrado, and eastern Pará: in the Belém Endemism Center of the Amazon biome more one municipality in the Cerrado. Specimens were collected in eight municipalities between 2010 and 2019 using quantitative and qualitative (active search) sampling methods. A total of 6,379 individuals were recorded, belonging to 14 genera and 22 species, distributed across five families. Pontoscolex corethrurus was the most abundant species, accounting for 81% of all specimens collected. Holoscolex fernandoi (6.4%) and Dichogaster bolaui (3.3%) were also frequently encountered. The remaining 16 species accounted for only 9.3% of the total abundance. These results highlight the dominance of Pontoscolex corethrurus, a peregrine species, indicating its strong adaptability to a wide range of environmental conditions. This study expands the knowledge of earthworm diversity in Brazil and underscores the need for further research on the ecological impacts of non-native species on the native fauna.